Katastrofy i wypadki w czasach romantyków (Instytut Badań Literackich Polskiej Akademii Nauk, 2024)
The first time I thought about the eponymous theme was when, on 12 September 2001, a day after the attack on World Trade Center, I saw a demonstration cortege on Krakowskie Przedmieście, led by a prominent politician; the participants carried placards with the sign ‘This is punishment for a world without God’ and sang religious hymns. I wondered which tradition to ascribe this event and the words on the placards to: Polish Romanticism, in which God is ready to blow up the planet, like Julian Ordon blew up the redoubt, in revenge for human evil, and in which Christ saves the European civilisation in extremis, striking its destructors with his glare, destructors such as Pankracy and his accomplices, the characters of Krasiński’s play. Or, did it belong directly to the everlasting imaginarium of the punishing divinity from which, to this day, all around the world, ideas are stemming, ideas which are providential in one way or another, and which allow the possibility of divine intervention: one that casts catastrophe on to humanity in response to unfavourable turns of earthly events, which humanity is guilty of?